Treatment efficacy for idiopathic recurrent pregnancy loss – a systematic review and meta‐analyses. (26th April 2018) - Rasmark Roepke, Emma; Hellgren, Margareta; Hjertberg, Ragnhild; Blomqvist, Lennart; Matthiesen, Leif; Henic, Emir; Lalitkumar, Sujata; Strandell, Annika
Abstract: Introduction: Medical treatment of women with idiopathic recurrent pregnancy loss is controversial. The objective was to assess the effects of different treatments on live birth rates and complications in women with unexplained recurrent pregnancy loss. Material and methods: We searched MEDLINE, Embase and the Cochrane Library, and identified 1415 publications. This systematic review included 21 randomized controlled trials regarding acetylsalicylic acid, low‐molecular‐weight heparin, progesterone, intravenous immunoglobulin or leukocyte immune therapy in women with three or more consecutive miscarriages of unknown cause. The study quality was assessed and data was extracted independently by at least two authors. Results: No significant difference in live birth rate was found when acetylsalicylic acid was compared with low‐molecular‐weight heparin or with placebo. Meta‐analyses of low‐molecular‐weight heparin vs. control found no significant differences in live birth rate [risk ratio (RR) 1.47, 95% CI 0.83–2.61]. Treatment with progesterone starting in the luteal phase seemed effective in increasing live birth rate (RR 1.18, 95% CI 1.09–1.27) but not when started after conception. Intravenous immunoglobulin showed no effect on live birth rate compared with placebo (RR 1.07, 95% CI 0.91–1.26). Paternal immunization compared with autologous immunization showed a significant difference in outcome (RR 1.8, 95% CI 1.34–2.41), although the studies were small and at high risk of bias. Conclusion: The literature does not allow advice on any specific treatment for idiopathic recurrent pregnancy loss, with the exception of progesterone starting from ovulation. We suggest that any treatment for recurrent pregnancy loss should be used within the context of a randomized controlled trial.